Resilient, healthy, and sustainable food systems for biodiversity conservation and use 2030 Action Targets: A global collection of good practice cases - Bioversity International; World Wildlife Fund International; Global Crop Diversity Trust; United Nations Environment Programme (Bioversity International and the International Center for Tropical Agriculture, 2022)
This guide is a showcase of good practices from around the world that use food systems as a pathway to meet many interconnected biodiversity-related targets in the Post-2020 Global Biodiversity Framework. Intended for practitioners and policymakers, it does not set out a ‘one size fits all’ approach but rather good practice examples that have the potential to be adapted and scaled in a variety of food systems around the world. The post-2020 Global Biodiversity Framework sets out an ambitious plan to implement broad-based action to transform society’s relationship with biodiversity, ensuring that by 2050 the shared vision of ‘living in harmony with nature’ is fulfilled. To live in harmony with nature and deliver food and livelihood security to millions of vulnerable people around the world, we must conserve and sustainably use biodiversity in our food systems, and better integrate and align efforts to conserve both agricultural and wild biodiversity rather than pursuing them separately.